Secreted frizzled-related protein 2 (sFRP2) redirects non-canonical Wnt signaling from Fz7 to Ror2 during vertebrate gastrulation - Brinkmann, Eva-Maria; Kumar, Rahul; Steinbeisser, Herbert; Kaufmann, Lilian; Özbek, Suat (The journal of biological chemistry, 2016)
Convergent extension movements during vertebrate gastrulation require a balanced activity of non-canonical Wnt signaling pathways, but the factors regulating this interplay on the molecular level are poorly characterized. Here we show that sFRP2, a member of the secreted frizzled-related protein (sFRP) family, is required for morphogenesis and papc expression during Xenopus gastrulation. We further provide evidence that sFRP2 redirects non-canonical Wnt signaling from Frizzled 7 (Fz7) to the receptor tyrosine kinase-like orphan receptor 2 (Ror2). During this process, sFRP2 promotes Ror2 signal transduction by stabilizing Wnt5a-Ror2 complexes at the membrane, whereas it inhibits Fz7 signaling, probably by blocking Fz7 receptor endocytosis. The cysteine-rich domain of sFRP2 is sufficient for Ror2 activation, and related sFRPs can substitute for this function. Notably, direct interaction of the two receptors via their cysteine-rich domains also promotes Ror2-mediated papc expression but inhibits Fz7 signaling. We propose that sFRPs can act as a molecular switch, channeling the signal input for different non-canonical Wnt pathways during vertebrate gastrulation.
Gesehen am 06.12.2018